The impact of diaphragmatic breathing on the endurance of contemporary dancers at the Institut Seni Budaya Indonesia Aceh: model-based experimental design - Sabri Gusmail; Prasika Dewi Nugra; Syahrizal Syahrizal (Institut Seni Indonesia Surakarta, 2023)
Managing dance movement elements is crucial for maintaining endurance and movement quality. The purpose of this study was to investigate the effects of applying diaphragmatic breathing on dancer endurance. The study employed a mixed-methods approach with an exploratory sequential design. The first phase, qualitative in nature, aimed to formulate hypotheses concerning the endurance issues faced by dancers in choreography courses. The second phase tested these hypotheses through experiments, incorporating control variables between two groups: Group 1, trained in dance movements using diaphragmatic breathing, and Group 2, solely trained in movements. The experiment took place at the Indonesian Institute of Cultural Arts in Aceh, with six female dancers enrolled in choreography classes randomly divided into two groups. None of the participants had prior experience with diaphragmatic breathing techniques while dancing. The study utilized a sphygmomanometer and oximetry for measurement. The endurance test involved dancing to a metronome for 5 minutes at tempos of 100, 110, and 120 without interruption. The results indicated that the respiratory frequency of dancers using diaphragmatic breathing was more stable compared to the group that did not employ this technique. These findings suggest that incorporating diaphragmatic breathing alternately while dancing can serve as a recommendation for maintaining dancers' endurance, particularly for students at the Indonesian Institute of Cultural Arts in Aceh.